All-electron density functional study on electronic structure, stability, and Ni-Ni bonding in polynuclear nickel complexes with bridging alkyne ligands - Koch, Jonas; Hyla-Kryspin, Isabella; Gleiter, Rolf; Klettke, Thomas; Walther, Dirk (Organometallics, 1999)
The method of density functional theory (DFT) has been used to study chain propagation reactions of zerovalent nickel complexes containing acetylene and σ-donor ligands. The calculations were carried out with all-electron basis sets of triple-ξ quality for the valence region and augmented with polarization functions. Gradient-optimized structures are compared with known experimental data. Stationary points on the potential energy surfaces are characterized by means of calculated vibrational analyses. Computed energetics of the aggregation reaction L2Ni(C2H2) + L‘2Ni(C2H2) → L2Ni(C2H2)NiL‘2 + C2H2 (2L = C2H2, L‘ = NH3 (2a); 2L = Ni(C2H2)2, 2L‘ = C2H2 (3a); 2L = 2L‘ = C2H2 (7); 2L = C2H2, 2L‘ = none (10); L = L‘ = PH3 (11), CO (12), none (13)) together with results of natural bond orbital (NBO) population analyses are used in the discussion of metal−metal bonding and the thermodynamic stability of acetylene-bridged polynuclear Ni(0) compounds. Ni−Ni interactions in 2a, 3a, 7, and 11−13 are compared with those in the hypothetical molecule [NiL2]2 (L = PH3 (9), 2L = C2H2 (10)) as well as with the d9−d9 system of the existing (μ-C2H2)[Ni(C5H5)]2 (8).
Gesehen am 10.11.2020